The Influence of different graft designs of intraoral bone blocks on volume gain in bone augmentation procedures: an in vitro study - Kalchthaler, Lukas; Kühle, Reinald; Büsch, Christopher; Hoffmann, Jürgen; Mertens, Christian (The international journal of oral & maxillofacial implants, 2020)
Lukas Kalchthaler, DDS/Reinald Kühle, MD, DDS/Christopher Büsch, MSc/Jürgen Hoffmann, MD, DDS/Christian Mertens, DDS: Purpose: Intraoral bone blocks from the external oblique are the gold standard for alveolar ridge bone grafting, but the - limited amount of available bone limits their use for larger defects. The objective of this study was to compare whether - different graft designs of intraoral bone blocks could affect the amount of bone gain. Materials and Methods: In this in - vitro study, 20 pig jaws were used to harvest bone blocks and subsequently augment single-wall bone defects. Each - bone graft was first used as a full block, and then the same block was divided lengthwise into two blocks, with one block - fixed at a distance as a cortical shell and the second block particulated to fill the gap between graft and bone. Three - stereolithographic (STL) files (pre-OP, full block, split block) were generated using an intraoral scanner. All STL files were - evaluated for volume gain and horizontal bone dimensions. Results: A mean volume gain of 0.36 cm2 (SD: 0.09) was - achieved for the full block and 0.78 cm2 (SD: 0.14) for the split block using the same block. The difference was statistically - significant (P < .0001). A mean horizontal bone gain of 4.37 mm (SD: 0.93) was achieved with a full block and 5.77 mm - (SD: 0.85) with the shell technique (P < .0001). Conclusion: With the same amount of bone removed, first as a full block - and then as a split block, the split-block technique achieved a significantly higher bone gain compared with the full-block - design.